COMPARISON AND ANALYSIS OF LEXICAL CHOICES IN E. FITZGERALD’S VS. E. HERON-ALLEN’S TRANSLATIONS OF OMAR KHAYYAM’S RUBAIYAT (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This study examines the lexical strategies employed by Edward FitzGerald and Edward Heron-Allen in their English translations of Omar Khayyam’s Rubáiyát. Using five quatrains from each translator, the research analyzes patterns in word choice, metaphorical density, imagery, and cultural specificity. FitzGerald’s translation exhibits a poetic, imaginative lexicon that prioritizes aesthetic dramatization, symbolic imagery, and universalized philosophical reflection, whereas Heron-Allen’s lexicon emphasizes literal accuracy, ethical clarity, and preservation of Persian cultural and religious context. The comparison illustrates how lexical decisions shape interpretive and emotional impact, highlighting the broader tension between creative adaptation and philological fidelity in literary translation.